2008
DOI: 10.5009/gnl.2008.2.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Sedation in Developing and Developed Countries

Abstract: Background/Aims: Data are scarce on endoscopic sedation practices outside the United States and Western Europe, particularly from developing nations. An Internet survey was used to assess endoscopic sedation practices in developing and developed countries. Methods: Responses to a Web-based survey of sedation practices from 165 expert endoscopists from 81 countries were analyzed. The most common sedation method was defined as that used for >50% of endoscopies within a country. Results: Responses were received f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 14 publications
(22 reference statements)
0
14
0
10
Order By: Relevance
“…[13] The use of sedation represents a standard for upper gastrointestinal endoscopies in developed countries. [14] Relieving pain and discomfort, eliminating anxiety, diminishing patient's memory of the procedure, and improving patient satisfaction and quality of examination are the objectives of sedation during endoscopy. [10] On the other hand, most of the cardiopulmonary side effects during the course of the procedure are related to sedation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] The use of sedation represents a standard for upper gastrointestinal endoscopies in developed countries. [14] Relieving pain and discomfort, eliminating anxiety, diminishing patient's memory of the procedure, and improving patient satisfaction and quality of examination are the objectives of sedation during endoscopy. [10] On the other hand, most of the cardiopulmonary side effects during the course of the procedure are related to sedation.…”
Section: Discussionmentioning
confidence: 99%
“…[22,23-25-28] It has been shown that the addition of ketamine to propofol allowed stable hemodynamics because of sympathomimetic effects of ketamine and reduced risk of hypoxemia even in pediatric patients with cardiac defects during procedural sedations. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]24] In a prospective randomized study by Nejati et al [25] , it was reported that hypotension and hypoxemia was not observed in two of 31 patients (6.45%) and apnea was observed in one of 31 patients (3.2%) during sedation for colonoscopy with a 1:1 mixture of ketamine and propofol. Tosun et al [12] found similar rate of hypoxemia (6.52%) and no hypotension with ketamine and propofol sedation in pediatric patients who underwent UGE.…”
Section: Discussionmentioning
confidence: 99%
“…The use of sedation for EGD varies from country to country and even differs within the same country because of social, cultural, economic, and regulatory influences [20]. Although EGD can be safely carried out without sedation, nowadays the vast majority of EGDs in developed countries are performed while the patient is sedated [10, 21, 22].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this, most of the adverse cardiopulmonary events during endoscopy are related to sedation [23]. The most common sedation regimen for EGD worldwide is propofol and midazolam with an opioid such as meperidine, and propofol use has been gaining in popularity because of increased endoscopist satisfaction compared to traditional sedation in recent years [10, 20, 22]. …”
Section: Discussionmentioning
confidence: 99%
“…In most instances, midazolam was used alone, although almost half of those surveyed indicated that propofol was used in some cases [11]. Benson reported similar findings regarding sedation practices in Africa and Asia, based upon a survey of 165 endoscopists practicing worldwide [12].…”
Section: Special Reportmentioning
confidence: 97%